Light from the Ancient Past, Vol. 1 : The Archaeological Background of the Hebrew-Christian Religion - Finegan, Jack, 1908-2000 (Book collections on Project MUSE., 1946)
A photograph, map, or diagram illustrates the text for every site described in this pilgrimage to Palestine, beginning with places connected with John the Baptist and proceeding to Bethlehem and Nazareth, Samaria and Galilee, Jerash, Caesarea, Jericho, the Mount of Olives, Jerusalem, and Emmaus. Each entry concludes with a brief bibliography of pertinent literature. Professor Finegan's knowledge of Christian theology and history plus his command of the archeology and topography of the Holy Land make his book an authoritative guide, a book for study and reference, and a volume for devotional reading. Originally published in 1969. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.